Uveal melanoma incidence trends in Canada: 1992–2010 vs. 2011–2017 - Conte, Santina; Lagacé, François; Ghazawi, Feras M.; Cattelan, Leila; Nath, Siddharth; Dhillon, Jobanpreet; Nedjar, Hacene; Rahme, Elham; Sasseville, Denis; Burnier, Miguel N.; Litvinov, Ivan V. (Frontiers in Medicine, 2023)
Background/Aims: Uveal melanoma is the most common type of non-cutaneous melanoma and the most common ocular malignancy in the adult population, especially affecting Caucasians (98% of cases). Despite its low incidence rate, we have noted increasing incidence trends in recent years. Methods: We analyzed uveal melanoma incidence data using the Canadian Cancer Registry for 2011-2017 years. The data was examined using the International Classification of Diseases for Oncology, Third Edition, codes for all uveal melanoma subtypes. The data for 2011-2017 was then compared to previously published work by our research group for uveal melanoma incidence in Canada between 1992-2010 using the same methodology. Results: Between 2011-2017, 1,215 patients were diagnosed with uveal melanoma, 49% of whom were females. The percentage distribution of uveal melanoma between the sexes was similar between 1992-2010 and 2011-2017, whereby of the 2,215 diagnoses of uveal melanoma in 1992-2010, 47.9% were females. The change in the incidence rate for this cancer has doubled between 1992-2010 and 2011-2017, from 0.074 to 0.15 cases per million individuals per year. Our study documents that the Canadian 2011-2017 age-standardized incidence rate (ASIR) for uveal melanoma against the World Health Organization (WHO) 2000-2025 world population standard was 5.09 cases per million individuals per year (95% confidence interval, 4.73-5.44), as compared with the 1992-2010 rate of 3.34 cases per million individuals per year (95% confidence interval, CI 3.20 to 3.47). Conclusion: This work demonstrates an ongoing, steady increase in uveal melanoma incidence in Canada in recent years.